Measurement of some Biochemical Values in Hemodialysis Patients in Baghdad - A.Hassan, Hiba (Iraqi Journal of Pharmaceutical Sciences, 2017)
One hundred of dialysis patients' mean age ( 51.18±8.28) years and one hundred healthy control group , where carried out from different hospitals of Baghdad city , during the period between November /2012 until March/2013. Blood samples were collected before dialyzing for estimation the concentration of urea, creatinine, uric acid, random blood sugar , calcium and cholesterol by enzymatic method detected spectrophotometerically.The aim of this study is to determine concentration of urea, creatinine, uric acid, RBS , calcium and cholesterol in hemodialysis patients in Baghdad . The results showed that there were highly significant increases (P<0.01) in the mean of creatinine , urea , uric acid and RBS for patients (587.86µmol/l , 25.57 mmol/l, 414.36mmol/l and 6.47mmol/l) compared to the mean of healthy control (88.60 µmol/l , 5.07mmol/l ,270.76mmol/l and 4.65mmol/l ) was detected . Also there was highly significant decrease(P< 0.01) in the mean of calcium and cholesterol for patients (1.93mmol/l and3.33mmol/l) compared to the mean of healthy control (2.34mmol/l and5.02mmol/l). It is concluded that in hemodialysis was associated with the higher levels of urea ,creatinine , uric acid and RBS with low level of cholesterol and calcium. Key words: RBS (random blood sugar), SUA (serum uric acid), Cholesterol, Urea, Creatinine